2010
DOI: 10.1124/jpet.110.173773
|View full text |Cite
|
Sign up to set email alerts
|

Drug Discrimination in Methamphetamine-Trained Rats: Effects of Cholinergic Nicotinic Compounds

Abstract: In drug interaction studies, varenicline served to dose-dependently attenuate the d-MAlike effects of (Ϫ)-nicotine, whereas mecamylamine, but not varenicline, reduced the discriminative stimulus effects of the training dose of d-MA. Differences between (Ϫ)-nicotine and other nicotinic agonists may be related to their ability to activate the DA system. These results provide further evidence that nicotinic mechanisms may be useful neurochemical targets for the development of therapeutics for the management of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
5

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 47 publications
5
46
5
Order By: Relevance
“…The comparable effects of these nicotinic full agonists are consistent with their similar nicotinic a4b2 subtype selectivity (see Table 1) and with previous drug discrimination data from nicotinetrained rodents (Reavill et al, 1987;Damaj et al, 1994). They contrast somewhat with data from MA-trained rats in which only nicotine fully substituted for the training dose of MA (Desai and Bergman, 2010). In those studies, 0.001 mg/kg of both (1)-epibatidine and (2)-epibatidine produced approximately 60 to 70% responding on the MA-associated lever, whereas a 3-fold increase in the dose of both enantiomers completely eliminated responding, precluding further testing.…”
Section: Discussioncontrasting
confidence: 29%
See 3 more Smart Citations
“…The comparable effects of these nicotinic full agonists are consistent with their similar nicotinic a4b2 subtype selectivity (see Table 1) and with previous drug discrimination data from nicotinetrained rodents (Reavill et al, 1987;Damaj et al, 1994). They contrast somewhat with data from MA-trained rats in which only nicotine fully substituted for the training dose of MA (Desai and Bergman, 2010). In those studies, 0.001 mg/kg of both (1)-epibatidine and (2)-epibatidine produced approximately 60 to 70% responding on the MA-associated lever, whereas a 3-fold increase in the dose of both enantiomers completely eliminated responding, precluding further testing.…”
Section: Discussioncontrasting
confidence: 29%
“…Varenicline previously has been characterized as a nicotinic partial agonist at the a4b2 receptor subtype (Rollema et al, 2007(Rollema et al, , 2010 and, depending on experimental conditions, may substitute partially or fully for nicotine in nicotine-trained rats and monkeys (Rollema et al, 2007;Smith et al, 2007;LeSage et al, 2009;Jutkiewicz et al, 2011;Cunningham et al, 2012). The plateau in the dose-effect function for varenicline at an intermediate level of responding on the MA-associated lever in the present experiments, in conjunction with its ability to antagonize the stimulant effects of nicotine in MA-trained rodents (Desai and Bergman, 2010), is consistent with its characterization as a nicotinic partial agonist.…”
Section: Drugmentioning
confidence: 56%
See 2 more Smart Citations
“…For d-AMPH, a dose of 0.5 mg/kg produces an increase in working memory performance, whereas a 2 mg/kg dose produces a decrease. d-METH on the other hand has little effect at 0.5 mg/kg, producing the highest increase at 2 mg/kg and 902 only decreasing at 4 mg/kg (Shoblock et al, 2003a (Desai and Bergman, 2010) and also causes dosedependent increases in METH-appropriate responding in humans who have learned to discriminate 10 mg METH from placebo (Sevak et al, 2009), suggesting that the subjective effects are also very similar, if not indistinguishable. Recently, it was also shown that varying doses (between 12 and 50 mg intranasally) of d-AMPH or METH produce similar subjective effects and did not differ from each other with regards to the rate at which participants would opt for a cash reward instead of a dose of the drug (Kirkpatrick et al, 2012), thereby not corroborating the notion that METH is more addictive or reinforcing than d-AMPH.…”
Section: Comparison Of the Mechanisms Of Action Of Amphetamine Versusmentioning
confidence: 90%